Comparing Strategies Targeting Osteoporosis to Prevent Fractures After an Upper Extremity Fracture (C‐STOP Trial): A Randomized Controlled Trial. (22nd August 2018) - Majumdar, Sumit R; McAlister, Finlay A; Johnson, Jeffrey A; Rowe, Brian H; Bellerose, Debbie; Hassan, Imran; Lier, Douglas A; Li, Stephanie; Maksymowych, Walter P; Menon, Matthew; Russell, Anthony S; Wirzba, Brian; et al.
ABSTRACT: We compared osteoporosis care after upper extremity fragility fracture using a low‐intensity Fracture Liaison Service (FLS) versus a high‐intensity FLS in a pragmatic patient‐level parallel‐arm comparative effectiveness trial undertaken at a Canadian academic hospital. A low‐intensity FLS (active‐control) that identified patients and notified primary care providers was compared to a high‐intensity FLS (case manager) where a specially‐trained nurse identified patients, investigated bone health, and initiated appropriate treatment. A total of 361 community‐dwelling participants 50 years or older with upper extremity fractures who were not on bisphosphonate treatment were included; 350 (97%) participants completed 6‐month follow‐up undertaken by assessors blinded to group allocation. The primary outcome was difference in bisphosphonate treatment between groups 6 months postfracture; secondary outcomes included differences in bone mineral density (BMD) testing and a predefined composite measure termed "appropriate care" (taking or making an informed decision to decline medication for those with low BMD; not taking bisphosphonate treatment for those with normal BMD). Absolute differences (%), relative risks (RR with 95% confidence intervals [CIs]), number‐needed‐to‐treat (NNT), and direct costs were compared. A total of 181 participants were randomized to active‐control and 180 to case‐manager using computer‐generated randomization; the groups were similar on study entry. At 6 months, 51 (28%) active‐control versus 86 (48%) case‐manager participants started bisphosphonate treatment (20% absolute difference; RR 1.70; 95% CI, 1.28 to 2.24; p  < 0.0001; NNT = 5). Of active‐controls, 108 (62%) underwent BMD testing compared to 128 (73%) case‐managed patients (11% absolute difference; RR 1.17; 95% CI, 1.01 to 1.36; p  = 0.03). Appropriate care was received by 76 (44%) active‐controls and 133 (76%) case‐managed participants (32% absolute difference; RR 1.73; 95% CI, 1.43 to 2.09; p  < 0.0001). The direct cost per participant was $18 Canadian (CDN) for the active‐control intervention compared to $66 CDN for the case‐manager intervention. In summary, case‐management led to substantially greater improvements in bisphosphonate treatment and appropriate care within 6 months of fracture than the active control. © 2018 American Society for Bone and Mineral Research.